Aerosol and droplet generation from performing with woodwind and brass instruments. Issue 11 (2nd November 2021) - McCarthy, Lauren P.; Orton, Christopher M.; Watson, Natalie A.; Gregson, Florence K. A.; Haddrell, Allen E.; Browne, William J.; Calder, James D.; Costello, Declan; Reid, Jonathan P.; Shah, Pallav L.; Bzdek, Bryan R.
Abstract: The performing arts have been significantly restricted due to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. We report measurements of aerosol and droplet concentrations generated when playing woodwind and brass instruments and comparisons with breathing, speaking, and singing. These measurements were conducted in a room with zero number concentration aerosol background in the 0.5-20 µm diameter size range, allowing clear attribution of detected particles to specific activities. A total of 13 instruments were examined across 9 participants. Respirable particle number concentrations and size distributions for playing instruments are consistent with those from the participant when breathing, based on measurements with multiple participants playing the flute and piccolo as well as measurements across the entire cohort. Due to substantial interparticipant variability, we do not provide a comparative assessment of the aerosol generated by playing different instruments, instead considering only the variation in aerosol yield across all instruments studied. Both particle number and mass concentrations from playing instruments are lower than those from speaking and singing at high volume, and no large droplets >20 µm diameter are detected. Combined, these observations suggest that playing instruments generates less aerosol than speaking or singing at high volumes. Moreover, there is no difference between the aerosol concentrations generated by professional and amateur performers while breathing, speaking, or singing, suggesting conclusions for professional singers may also apply to amateurs.